Square wave voltammetry of TNT at gold electrodes modified with self-assembled monolayers containing aromatic structures. - Scott A Trammell; Dan Zabetakis; Martin Moore; Jasenka Verbarg; David A Stenger (PLoS ONE, 2014)
Square wave voltammetry for the reduction of 2,4,6-trinitrotoluene (TNT) was measured in 100 mM potassium phosphate buffer (pH 8) at gold electrodes modified with self-assembled monolayers (SAMs) containing either an alkane thiol or aromatic ring thiol structures. At 15 Hz, the electrochemical sensitivity (µA/ppm) was similar for all SAMs tested. However, at 60 Hz, the SAMs containing aromatic structures had a greater sensitivity than the alkane thiol SAM. In fact, the alkane thiol SAM had a decrease in sensitivity at the higher frequency. When comparing the electrochemical response between simulations and experimental data, a general trend was observed in which most of the SAMs had similar heterogeneous rate constants within experimental error for the reduction of TNT. This most likely describes a rate limiting step for the reduction of TNT. However, in the case of the alkane SAM at higher frequency, the decrease in sensitivity suggests that the rate limiting step in this case may be electron tunneling through the SAM. Our results show that SAMs containing aromatic rings increased the sensitivity for the reduction of TNT when higher frequencies were employed and at the same time suppressed the electrochemical reduction of dissolved oxygen.